2011
DOI: 10.1016/j.neuropharm.2011.05.020
|View full text |Cite
|
Sign up to set email alerts
|

The wake-promoting transmitter histamine preferentially enhances alpha-4 subunit-containing GABAA receptors

Abstract: Histamine is an important wake-promoting neurotransmitter that activates seven-transmembrane G-protein coupled histamine receptors. However, histamine demonstrates target promiscuity, including direct interaction with the structurally unrelated glutamate (NMDA) and GABAA receptor channels. Previous work showed that histamine enhances the activity of recombinant GABAA receptor isoforms typically found in synaptic locations, although co-release of histamine and GABA is not known to occur in vivo. Here we used pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 69 publications
1
12
0
Order By: Relevance
“…Our study confirms the recent finding ( Saras et al, 2008 ; Bianchi et al, 2011 ) that there is a robust modulatory effect of histamine on GABA A Rs with different subunit combinations. The screening of point mutated GABA A R subunits revealed that most mutations, which encompass several amino acids conserved in β subunits, did not influence histamine potentiation.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Our study confirms the recent finding ( Saras et al, 2008 ; Bianchi et al, 2011 ) that there is a robust modulatory effect of histamine on GABA A Rs with different subunit combinations. The screening of point mutated GABA A R subunits revealed that most mutations, which encompass several amino acids conserved in β subunits, did not influence histamine potentiation.…”
Section: Discussionsupporting
confidence: 93%
“…These subunits are α1–6, β1–3, γ1–3, δ, ε, 𝜃, π, and ρ1–3. Bianchi et al (2011) showed α subunit preference of histamine under low GABA concentrations.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pregnanolone, one of the main neurosteroids produced in the brain of hyperamonemic rats (Cauli et al 2009) inhibits α4-containing receptors in contrast to its stimulatory effect at other GABAA receptors (Adkins et al, 2001). GABAA receptors containing the α4-subunit behave pharmacologically different than GABAA receptors containing α1-, α2-, α3 subunits, for example at the benzodiazepine-site (Olsen and Sieghart, 2009;Adkins et al, 2001), for sensitivity to ethanol (Hanchar et al, 2006) or to taurine or histamine (Bianchi et al, 2011).…”
Section: Increased Levels Of Extracellular Gaba and Of Neurosteroids mentioning
confidence: 99%